MSME Sustainability Through the Implementation of Management Accounting with Knowledge as a Moderation Variable - Dwi Puryati; Thalita Zherlyn; Ariya Nur Alief (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2025)
This study examines the influence of the implementation of management accounting practices on the performance of micro, small, and medium enterprises (MSMEs) in the City of Bandung as well as the role of management accounting knowledge as a moderation variable. This research has a novelty of the approach used, which combines the indicators of the four stages of management accounting according to the International Federation of Accountants (IFAC). The method used was a quantitative survey with data obtained through questionnaires from 176 MSME actors. Data analysis used multiple linear regression to examine the relationship between management accounting practices and MSME performance, with knowledge as a moderation variable. The results of the analysis showed that decision-making and quality management practices had a positive and significant effect on the performance of MSMEs, while costing, budgeting, controlling, and capital budgeting practices did not have a significant influence. Knowledge of management accounting strengthens the relationship between management accounting practices and MSME performance. This study has limitations only in the Bandung City area with an unbalanced number of respondents in proportion between micro, small, and medium companies. The implications of this study highlight the importance of increasing management accounting literacy and mentoring for MSMEs to increase business competitiveness and sustainability. Abstrak - Penelitian ini mengkaji pengaruh implementasi praktik akuntansi manajemen terhadap kinerja usaha mikro, kecil, dan menengah (UMKM) di Kota Bandung serta peran pengetahuan akuntansi manajemen sebagai variabel moderasi. Penelitian ini mempunyai kebaruan dari pendekatan yang digunakan yaitu menggabungkan indikator empat tahapan akuntansi manajemen menurut International Federation of Accountants (IFAC). Metode yang digunakan adalah survei kuantitatif dengan data yang diperoleh melalui kueseioner dari 176 pelaku UMKM. Analisis data menggunakan regresi linier berganda untuk menguji hubungan anatara praktik akuntansi manajemen dan kinerja UMKM dengan pengetahuan sebagai variabel moderasi. Hasil analisis menunjukkan bahwa praktik pengambilan keputusan dan manajemen kualitas berpengaruh positif dan signifikan terhadap kinerja UMKM, sementara praktik costing, budgeting, controlling, dan capital budgeting tidak memberikan pengaruh yang signifikan. Pengetahuan akuntansi manajemen memperkuat hubungan praktik akuntansi manajemen terhadap kinerja UMKM. Penelitian ini mempunyai keterbatasan hanya dilakukan pada wilayah Kota Bandung dengan jumlah responden yang tidak seimbang proporsinya antara perusahaan mikro, kecil, dan menengah. Implikasi penelitian ini menyoroti pentingnya peningkatan literasi akuntansi manajemen serta pendampingan bagi UMKM untuk meningkatkan daya saing dan keberlanjutan usaha.